2014
DOI: 10.1186/1751-0759-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender, age, family support, and treatment on perceived stress and coping of patients with type 2 diabetes mellitus

Abstract: BackgroundWe previously found that the empowerment of patients with type 2 diabetes mellitus can be strongly affected by gender and age in addition to self-managed diet and exercise behaviors and treatment. This study was to examine the effects of gender, age, family support, and treatment on the perceived stress and coping of patients with type 2 diabetes mellitus living with family.MethodsA survey was conducted of 140 adults with type 2 diabetes mellitus who were living with family. There was no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 15 publications
2
24
0
2
Order By: Relevance
“…Our studies of patients with type 2 diabetes mellitus in the past confirm that the psychological impact of diabetes scale correlates well with HbA1c levels and treatment methods, reflecting anxieties routinely felt by patients 9,10 . Some questions remain, however, as to what aspects of the patients' everyday anxieties are affected by HbA1c levels and treatment methods, or whether patient empowerment education is sufficient to alleviate the psychological impacts felt by the patients.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our studies of patients with type 2 diabetes mellitus in the past confirm that the psychological impact of diabetes scale correlates well with HbA1c levels and treatment methods, reflecting anxieties routinely felt by patients 9,10 . Some questions remain, however, as to what aspects of the patients' everyday anxieties are affected by HbA1c levels and treatment methods, or whether patient empowerment education is sufficient to alleviate the psychological impacts felt by the patients.…”
Section: Discussionsupporting
confidence: 68%
“…With respect to impact from diabetes (S1), for which a sex difference was particularly noticeable, it was suggested that women were particularly sensitive to the psychological impact caused by diabetes, because significance disappeared after adjustments by sex, disease duration, glycemic control and number of ( Figure 1a), and stratification by age showed significance only in women ( Table 2). In an earlier study that we carried out into perceived stress and coping behaviors in 140 type 2 diabetes patients aged 40 years or older 10 , factor analysis identified clear sex differences in perceived stress and coping among these patients: relative to men, women were always aware of the psychological stress of having diabetes, but their coping was passive, with the 50-69 years age group showing the lowest level of self-awareness, sense of responsibility or self-empowerment relating to diabetes. The sex difference in perceived stress and coping was assumed to be a result of social, innate and situational factors 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Hara et al. () found that male patients with T2DM living with their spouses exhibited better coping skills to deal with the stress from the disease compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, some studies illustrate the importance of family coping on adherence to T2DM treatment and showed an association between coping and metabolic control (Gafvels & Wandell, 2006). Hara et al (2014) found that male patients with T2DM living with their spouses exhibited better coping skills to deal with the stress from the disease compared to females. *** p < .001; ** p < .01; * p < .05 Moreover, higher levels of partner positive support (e.g., encouragement, remembrance, congratulations, planning) from the patients' perspective at T1 predicted higher levels of adherence to glucose monitoring at T2.…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence has also been increasing across the world. 3 According to The Turkish epidemiology survey of diabetes, hypertension, obesity and endocrine disease (TURDEP-II), incidence of diabetes has reached up to 13.7% in Turkish adult population. 4 Diabetes being common in the society is an important public health concern because it leads to economic losses, its complications seriously influence life quality of the patient, and it has high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%